Pemanfaatan Media Bimbingan dan Konseling pada Aspek Karier, Pribadi, Sosial, dan Belajar: Studi Literatur : Penelitian - Triska Aulia Viranti (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The increasingly dynamic development of students due to social change and technological advancement requires school guidance and counseling services to adapt through the use of relevant and innovative media. This study aims to present a systematic literature review on the use of guidance and counseling media in supporting four domains of student development: personal, social, learning, and career. A systematic literature review method was employed following the PRISMA. Data analysis was conducted using descriptive quantitative analysis and narrative synthesis. The findings reveal a significant shift from traditional print media toward interactive digital and web-based media in school guidance and counseling services. Digital and web-based media are predominantly used to support career and learning development, while audiovisual media and social media are more commonly applied to enhance personal and social development. However, existing studies remain fragmented and often focus on a single type of media or a specific developmental domain. This review highlights the need for integrative approaches and more rigorous research designs to strengthen evidence-based media utilization in school guidance and counseling practices.